Optimasi Pemanfaatan Energi Alternatif Berbasis Hybrid di Desa Sembalun Bumbung, Kabupaten Lombok Timur - Agung Budi Muljono; Hendra Sasmita; Adi Purna (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2023)
As one of the islands in Indonesia that has the potential for Hydropower, PV and Biogas on Lombok Island, to be precise, these three alternative generators can be utilized in Sembalun District, Sembalun Bumbung Village, which is supported by the fast-flowing Mayung Puteq River. Apart from that, many residents of this area make their living as livestock breeders, and automatically Sembalun Bumbung village has a lot of livestock so that their waste can be used as biogas energy, therefore this alternative energy can be used to help supply electrical energy in the area. This paper presents an analysis of optimal power supply system type options for remote areas using HOMER software. The type of system that will be used is PV/Battery/converter/Biomas/Hydro. Selected system types are ranked based on total net present cost (NPC). Then the smallest total NPC is the best option. From the selected system type, the system configuration will be known, namely the number and capacity of each component. From the simulation results of the Hydro-PV-Biogas configuration using HOMER on a Hybrid power plant equipped with batteries, it was found that the system development planning was appropriate with a total annual energy of 1,035,240 kWh/year. With an NPC cost breakdown of $127,018; selling price of energy (COE) of $ 0.010/kWh and operational costs of $ 8,841/year, this provides a technical and economic outlook that is feasible for developing its implementation.